Culture, society and sexuality: a reader - Parker, Richard G.; Aggleton, Peter (Social aspects of AIDS, 1999)
Since the beginnings of time, people have been interested in sex - the form it takes, the pleasure it can give, the circumstances in which it occurs, and what it means - both for the individuals concerned and to society more generally. Often seen as a synonym for love, sometimes as an expression of power, and infrequently as a means of exploitation and abuse, sex is a complex and multi-faceted aspect of human behaviour that has been written about by numerous writers and theorists worldwide. This book offers an introduction to the central debates in sexuality research. Among the issues examined are the social and cultural dimensions of sex, human sexuality and sex research. It will be of use to students of sociology, cultural studies, and health and behavioural studies.
Keywords: LGBTQIA2+; VIH; approches et analyses; cours; discipline; hétérosexisme; identités LGBTQIA2+; premier cycle; queer; ressource en ligne; santé; sciences humaines; sex1920; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques

Les études gay et lesbiennes - Eribon, Didier (Supplémentaires, 1998)
Depuis une quinzaine d'années se sont développées dans l'université américaine ce qu'il est désormais convenu d'appeler les Gay and Lesbian Studies. Il s'agit non seulement de redécouvrir le passé occulté des cultures homosexuelles, mais aussi et surtout de reconsidérer l'histoire et le présent de la sexualité en général et la manière dont chaque société et chaque époque l'organisent et la réglementent. Ces nouvelles études ont très vite essaimé dans le monde anglo-saxon et dans presque toute l'Europe. Tout en étant en France au coeur de nombreuses polémiques, elles restent étrangement peu connues. Le colloque du Centre Georges Pompidou, les 25 et 27 Juin 1997, avait pour objectif de donner la parole à quelques-un.e.s des plus éminent.e.s représentant.e.s nord-américain.e.s de ce champ de pensée afin qu'iels puissent présenter leurs travaux au public français. Il a permis de découvrir non seulement leur richesse et leur diversité mais aussi, le cas échéant, les divergences qui pouvaient exister dans leurs approches. Des chercheureuses français.e.s et européen.nes participaient également à ces journées de discussion, pour engager le dialogue critique avec ces intellectuel.les américain.e.s. Une occasion d'ouvrir la voie à ce que pourrait être, en France, un travail de recherche sur les questions posées par le mouvement gay et lesbien à l'ensemble de la vie politique, culturelle et universitaire.
Keywords: 1900-1999; 1980-1989; 1990-1999; amériques; approches et analyses; cours; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; régions géographiques; sexisme; sexualité; soc2014; systèmes d'oppressions; thématiques; états-unis

Le sexe du savoir - Le Doeuff, Michèle (Aubier, 1998)
Le savoir est-il l'apanage du sexe masculin? L'auteur, chargée de recherches au CNRS, fait ici la généalogie des mythes qui sexualisent le savoir et donc le pouvoir. Sur un ton polémique et drôle, elle propose un parcours original dans l'histoire de la philosophie et de la littérature, mais aussi dans l'actualité.
Keywords: approches et analyses; cours; discipline; fem1000; genre; identités LGBTQIA2+; misogynie; philosophie; premier cycle; sciences humaines; sexisme; systèmes d'oppressions; thématiques

Dangerous liaisons: gender, nation and postcolonial perspectives - McClintock, Anne; Shohat, Ella; Mufti, Aamir Rashid (Cultural politics, 1997)
This collection addresses the issues raised by the postcolonial condition, considering nationhood, history, gender and identity from an interdisciplinary perspective.
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; discours dominant; féminisme décolonial; histoire et politique; identités LGBTQIA2+; intersectionnalité; inégalités; lit4700; militance; poésie; premier cycle; queer; racisme; sexisme; systèmes d'oppressions; thématiques; études culturelles; études littéraires

Women and gender in Islam: Historical roots of a modern debate - Ahmed, Leila (Yale University Press., 1992)
Explores the historical roots of the debate about women in Islamic societies by tracing the developments in Islamic discourses on women and gender up to the present. The book describes the gender systems in place in the Middle East both before and after the rise of Islam.
Keywords: 1800-1899; 1900-1999; approches et analyses; asie; cours; cycles supérieurs; discipline; fem1000; fem7000; femmes* musulmanes; féminisme islamique; genre; histoire; identités LGBTQIA2+; islam; lit3220; moyen-âge; orient; premier cycle; périodes historiques; rapports de domination; rapports sociaux de sexe; religion; ressource en ligne; régions géographiques; science des religions; sciences humaines; sexisme; sociologie; syrie; systèmes d'oppressions; thématiques; théologie; voiles islamiques

Dykewords: An anthology of lesbian writings - Lesbian Writing and Publishing Collective. (Women's Press, 1990)
An entertaining and refreshing anthology that includes writing about the vibration of lesbian love, cultural identity, sexual fantasy, overcoming alcohol abuse, a teenage coming out, lesbian history, imaginative lesbian antics for lesbian survival and much, much more
Keywords: anthologie; approches et analyses; corps; histoire et politique; identités LGBTQIA2+; littérature; outils; ouvrages de références; personnes lesbiennes; poésie; racisme; ressource en ligne; roman; santé; sexisme; sexualité; système colonial; systèmes d'oppressions; thématiques

« Oppression, » dans The politics of reality, - Frye, Marilyn (The politics of reality: essays in feminist theory, 1983)
Politics of Reality includes nine essays that examine sexism, the exploitation of women, the gay rights movement and other topics from a feminist perspective. The essays "The Problem That Has No Name" and "A Note On Anger" have been translated into Spanish by Maria Lugones for circulation in la Asociacion Argentina de Mujeres en Filosofia.
Keywords: 1900-1999; 1970-1979; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; identités LGBTQIA2+; intersectionnalité; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; états-unis

Un choix sans equivoque : recherches historiques sur les relations amoureuses entre les femmes : XVIe-XXe siecle - Bonnet, Marie-Jo (Femme, 1981)
C'est le fruit de recherches menées pour une thèse de doctorat de 3e cycle. Etude détaillée, même érudite, mais de lecture facile. Importante bibliographie.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; LGBTQIA2+; amour lesbien; approches et analyses; cours; discipline; discours dominant; his4860; histoire; histoire de la sexualité; histoire des femmes*; histoire et politique; hétérosexisme; identités LGBTQIA2+; lesbianisme; lesbiennes; premier cycle; périodes historiques; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; sexisme; sexologie; sexualité; sexualité lesbienne; sexualités dissidentes; systèmes d'oppressions; thématiques

Old mistresses: Women, art and ideology - Parker, Rozsika; Pollock, Griselda (Pantheon Books, 1981)
How was it possible, by the later twentieth century, to have erased women as artists from art history so comprehensively that the idea of 'the artist' was exclusively masculine? Why was this erasure more radical in the twentieth century than ever before? Why is everything that compromises greatness in art coded as 'feminine'? Has the feminist critique of Art History yet effected real change? With a new Preface by Griselda Pollock, this new edition of a truly groundbreaking book offers a radical challenge to a women-free Art History. Parker and Pollock's critique of Art History's sexism leads to expanded, inclusive readings of the art of the past. They demonstrate how the changing historical social realities of gender relations and women artists' translation of gendered conditions into their works provide keys to novel understandings of why we might study the art of the past. They go further to show how such knowledge enables us to understand art by contemporary artists who are women and can contribute to the changing self-perception and creative work of artists today.
Keywords: LGBTQIA2+; approches et analyses; art féministe; arts; cours; discipline; fem1000; genre; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; premier cycle; sexisme; stéréotypes; systèmes d'oppressions; thématiques